Mesalazine-Induced Acute Pancreatitis in Inflammatory Bowel Disease Patients: A Systematic Review - Pan J; Li Z; Ye C; Zhang X; Yang Q; Zhang X; Zhou Y; Zhang J (Therapeutics and Clinical Risk Management)
Juan Pan,1,* Zuyi Li,1,* Chao Ye,2 Xiaojuan Zhang,1 Qiongliang Yang,1 Xu Zhang,1 Ya Zhou,3 Jianjun Zhang2 1Department of Pharmacy, Liuyang Hospital of Traditional Chinese Medicine, Changsha, Hunan, 410300, People’s Republic of China; 2Department of Pharmacy, Guangdong Provincial second Hospital of Traditional Chinese Medicine (Guangdong Provincial Engineering Technology Research Institute of Traditional Chinese Medicine), Guangzhou, Guangdong, 510095, People’s Republic of China; 3Department of Pharmacy, People’s Hospital of Ningxiang City Affiliated to Hunan University of Chinese Medicine, Changsha, Hunan, 410600, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chao Ye, Department of Pharmacy, Guangdong Provincial second Hospital of Traditional Chinese Medicine (Guangdong Provincial Engineering Technology Research Institute of Traditional Chinese Medicine), No. 60, Hengfu Road, Guangzhou, Guangdong, 510095, People’s Republic of China, Email yechao1234256@163.comObjective: Mesalazine is a widely used medication for treating mild to moderate inflammatory bowel disease (IBD). First identified as a potential cause of acute pancreatitis (AP) in 1989, the link between mesalazine and AP has primarily been established through case reports and a limited number of retrospective studies. This study aims to explore the characteristics of mesalazine-induced AP.Methods: The databases of CNKI, Wanfang Data, VIP, PubMed and Web of Science were searched (up to March, 2024), and the case reports of mesalazine-related AP in IBD patients were collected and descriptively analyzed.Results: Thirty-four reports were included, describing 42 patients (22 males, 16 females, 4 unspecified) with mesalazine-related AP. The onset of pancreatitis occurred a median of 14 days (range 1– 730 days) after starting mesalazine. Common symptoms included abdominal pain (100%), vomiting (38.1%), fever (21.4%), and nausea (21.4%). Most patients had elevated serum amylase and lipase levels, with some showing raised C-reactive protein and erythrocyte sedimentation rate. Imaging tests, such as computed tomography and B-scan ultrasonography, revealed edematous infiltration and inflammation. Discontinuation of mesalazine led to symptom resolution in all patients, with 93.3% improving within a week. Alternative treatments or switching to other forms of 5-aminosalicylic acid may be considered for ongoing management. Rechallenge with mesalazine led to recurrence of AP in 21 cases, with a shorter median time to symptom onset.Conclusion: Mesalazine-induced AP is a rare but significant adverse reaction, not related to drug dosage, and can occur at any point during treatment, typically within two weeks. The reaction can recur upon rechallenge. Discontinuation of mesalazine and symptomatic treatment typically resolves the condition.Keywords: mesalazine, acute pancreatitis, adverse drug reactions, clinical characteristics, systematic review